Effectiveness of NSP enzyme and organic chromium supplementation in low-protein feed on carbohydrate utilization in Pomfret Colossoma macropomum - Maihardiyanti Faiqotul Himmah; Ichsan Achmad Fauzi; Julie Ekasari; Muhammad Raditya Gumelar; Muhammad Agus Suprayudi (Jurnal Akuakultur Indonesia)
This study aims to evaluate the effectiveness of NSP enzyme and organic chromium supplementation in low-protein Colosoma macropomum diet to increase carbohydrate utilization. The diets contains isoprotein (20%) and isoenergy. Factorial design with two factors, namely NSP enzyme (0 and 1 g/kg) and organic chromium (0, 1, and 2 mg/kg). Fish are reared in an aquarium measuring 80 x 50 x 35 cm3 and containing 75 L of water and stock at the density of 15 fish and reared for 60 days. The test parameters used are postprandial blood glucose levels, antioxidant activity, glycogen in muscle and liver, and growth performance. The results showed that the highest postprandial blood glucose levels were when the NSP enzyme was administered. Furthermore, the lowest malondialdehyde (MDA) values and the highest superoxide dismutase (SOD) and glutathione peroxide (GPx) values were obtained in fish fed feed containing 1 g/kg of NSP enzyme and 1 mg/kg organic chromium. Fish fed feed containing 1 g/kg NSP enzyme and 1 mg/kg organic chromium showed significant values in liver and muscle glycogen as well as growth performance compared to other treatments. From this research, it can be concluded that supplementation of NSP enzyme and organic chromium at doses of 1 g and 1 mg per kg of feed produces the best growth performance and anti-oxidant capacity in pomfret fish.